2020
DOI: 10.1111/nph.16883
|View full text |Cite|
|
Sign up to set email alerts
|

A derivation error that affects carbon balance models exists in the current implementation of the modified Arrhenius function

Abstract: Carbon-concentration and carbon-climate feedbacks in CMIP6 models, and their comparison to CMIP5 models. Biogeosciences

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(13 citation statements)
references
References 55 publications
1
12
0
Order By: Relevance
“…1b). However, the results of Murphy & Stinziano (2020) in their Fig. 2 showed that there were often significant outliers in the plots of estimated parameter values (including k 25 ) of one model vs those of the other model.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…1b). However, the results of Murphy & Stinziano (2020) in their Fig. 2 showed that there were often significant outliers in the plots of estimated parameter values (including k 25 ) of one model vs those of the other model.…”
mentioning
confidence: 99%
“…Eqn 1 has also been used for the temperature response of photosynthetic CO 2 -diffusion parameters, mesophyll conductance (Bernacchi et al, 2002) and bundle sheath conductance (Yin et al, 2016). However, recently Murphy & Stinziano (2020) drew our attention to the original modified Arrhenius equation (Johnson et al, 1942), which, if expressed in a form similar to Eqn 1 with the parameter value at the reference temperature of 25°C, is as follows:…”
mentioning
confidence: 99%
See 3 more Smart Citations